EDUKASI PENCEGAHAN PENYAKIT ISPA DALAM MENINGKATKAN PENGETAHUAN, SIKAP, PERILAKU DAN POLA ASUH ORANG TUA PADA BALITA DI DESA CINTA DAMAI KABUPATEN BENER MERIAH - Indah Saputri; Zulfikar; Nurlaely HS (Aceh Health Sciences Journal, 2025)
Acute Respiratory Tract Infection (ARI) is one of the main causes of morbidity and mortality in toddlers in Indonesia. Low parental knowledge and parenting patterns are important factors contributing to the high number of ARI cases. This study aims to determine the effect of health education on improving parental knowledge, attitudes, behaviors, and parenting patterns in preventing ARI in toddlers. The study used a pre-experimental method with a one-group pretest-posttest design in Cinta Damai Village, Bener Meriah Regency. The sample consisted of 34 parents of toddlers taken using a total sampling technique. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis used a t-test (Paired Sample t-test). The results showed a significant increase after being given health education (p = 0.000 < 0.05). Knowledge increased from 60% to 93.3%, attitudes from 56.7% to 93.3%, behavior from 50% to 90%, and parenting patterns from 50% to 96.7%. Conclusion: Health education significantly impacts parental knowledge, attitudes, behaviors, and parenting practices in preventing acute respiratory infections (ARI) in toddlers. Health workers are expected to continue conducting regular educational activities to increase awareness and foster an active role for parents in maintaining toddler health. Keywords: Health Education, ARI, Knowledge, Attitude, Behavior, Parenting